Nominalized Matter: Agency of Material. (September 2014) - Baerlecken, Daniel; Wright, Katherine Blair
This paper investigates making as a process that brings together diverse materials and combines their flow in anticipation of what might emerge. Ingold calls this approach the textility of making, which gives priority to the formation of materials as a process, in which form is generated through interventions within fields of forces and currents of materials – not through a predefined notion of an ideal outcome. The approach opposes the Aristotelian hylomorphic approach, which focuses on final products. This paper investigates textiles techniques and their potential for simultaneously creating ornamental and structural systems. This work is conducted through a sequence of architecture design studios, producing the case studies found in this paper. Within the paper different examples of textile systems are introduced ranging from a Semperian approach (wall as dress) to form finding experiments with active textile materials – demonstrating the potential for methods utilizing material agency to inform architectural design.